PENGARUH DPK DAN NPL TERHADAP PENYALURAN KREDIT PADA PT BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, Tbk PERIODE 2019–2021 - R. Deden Adhianto; Fitria Rahmadani (JEBS (Journal of Economic and Business Student), 2022)
ABSTRACT This study aims to determine the development of Third Party Funds (DPK), Non Performing Loans (NPL), Credit Distribution, and the influence of Third Party Funds (DPK) and Non Performing Loans (NPL) on lending (Credit Distribution) at bank bjb for the period 2019-2021. The research method is quantitative, with analysis of classical assumption test data, multiple linear regression, Coefficient of Determination, F-Test and T-Test. Secondary data comes from bank bjb's quarterly financial statements for the period 2019-2022. Research shows that the development of Third Party Funds (DPK) and Non-Performing Loans (NPL) has fluctuated, while Credit Distribution has increased each period. Simultaneously Third Party Funds (DPK) and Non-Performing Loans (NPL) have a significant effect on Credit Distribution. Partially, Third Party Funds (TPF) have no significant effect on lending, while Non-Performing Loans (NPL) have a significant negative effect on lending. Keywords: Third Party Funds, Non Performing Loans, Credit Distribution